2023
DOI: 10.1002/apxr.202300099
|View full text |Cite
|
Sign up to set email alerts
|

The Anomalous Photo‐Nernst Effect of Massive Dirac Fermions In HfTe5

Maanwinder P. Singh,
Jonas Kiemle,
Chen Xu
et al.

Abstract: The quantum geometric Berry curvature results in an anomalous correction to the band velocity of crystal electrons with a corresponding transverse (thermo)electric conductivity. However, time‐reversal symmetry typically constrains the direct observation and exploitation of anomalous transport to magnetic compounds. Here, it is demonstrated the anomalous Hall and Nernst conductivities are essential for describing the optoelectronic transport in thin films of the non‐magnetic, weakly gapped semimetal HfTe5 subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Several studies provided evidence, including photoemission spectroscopy and electron transport, that the fundamental gaps of HfTe 5 , and similarly ZrTe 5 , can be strain-tuned across a weak to a strong topological insulator phase. ,,, Moreover, the location of additional, trivial carrier pockets depends on strain as well. , Therefore, our results may explain partly the considerable variation of results seen in the literature. While some studies reported a quasi-quantized Hall resistance of gapped Dirac Fermions with well-developed Shubnikov-de-Haas oscillations, , other studies reported signatures of anomalous Hall effects with largely suppressed Shubnikov-de-Haas oscillations, ,, sometimes even in nominally identical materials, and further studies described the transport features taking into account additional carrier pockets. Based on the substantial inhomogeneity of exfoliated films observed here, it may be advantageous to carefully and systematically differentiate between measurements on bulk crystal (mm-scale) and exfoliated films (μm-scale). We note that, in previous work on HfTe 5 , we already observed such systematic differences in the magnetotransport properties of bulk reference crystals and exfoliated films .…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…Several studies provided evidence, including photoemission spectroscopy and electron transport, that the fundamental gaps of HfTe 5 , and similarly ZrTe 5 , can be strain-tuned across a weak to a strong topological insulator phase. ,,, Moreover, the location of additional, trivial carrier pockets depends on strain as well. , Therefore, our results may explain partly the considerable variation of results seen in the literature. While some studies reported a quasi-quantized Hall resistance of gapped Dirac Fermions with well-developed Shubnikov-de-Haas oscillations, , other studies reported signatures of anomalous Hall effects with largely suppressed Shubnikov-de-Haas oscillations, ,, sometimes even in nominally identical materials, and further studies described the transport features taking into account additional carrier pockets. Based on the substantial inhomogeneity of exfoliated films observed here, it may be advantageous to carefully and systematically differentiate between measurements on bulk crystal (mm-scale) and exfoliated films (μm-scale). We note that, in previous work on HfTe 5 , we already observed such systematic differences in the magnetotransport properties of bulk reference crystals and exfoliated films .…”
Section: Discussionmentioning
confidence: 80%
“…While some studies reported a quasi-quantized Hall resistance of gapped Dirac Fermions with well-developed Shubnikov-de-Haas oscillations, , other studies reported signatures of anomalous Hall effects with largely suppressed Shubnikov-de-Haas oscillations, ,, sometimes even in nominally identical materials, and further studies described the transport features taking into account additional carrier pockets. Based on the substantial inhomogeneity of exfoliated films observed here, it may be advantageous to carefully and systematically differentiate between measurements on bulk crystal (mm-scale) and exfoliated films (μm-scale). We note that, in previous work on HfTe 5 , we already observed such systematic differences in the magnetotransport properties of bulk reference crystals and exfoliated films . Depending on the used contacts within a multiterminal, exfoliated device, one may probe homogeneous areas with little to no built-in strain or one may probe inhomogeneous areas, which might consist of patches with varying density, varying gap size, or even varying topological nature of the bands.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations